2017
DOI: 10.1002/psc.3009
|View full text |Cite
|
Sign up to set email alerts
|

Conformational latitude – activity relationship of KPPR tetrapeptide analogues toward their ability to inhibit binding of vascular endothelial growth factor 165 to neuropilin‐1

Abstract: Neuropilin-1 has been found to be overexpressed in several kinds of malignant tumors, and it is postulated that its interaction with the vascular endothelial growth factor 165 leads to progression of tumor vascularization and growth. Several analogues (KxxR) with various conformational latitudes have been synthesized and found as inhibitors of NRP-1. Detailed insight provided by molecular dynamics simulation allowed forming a clear relationship between flexibility of xx part of the molecule and its inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…It is possible that other ligands containing a C-terminal arginine will also bind in a similar fashion [15]. Although protein-protein interactions have been considered challenging targets in drug discovery [16], a number of small molecules and peptides have been identified as inhibitors of the VEGF-A 165 -NRP1 interaction [17][18][19][20][21][22][23][24][25][26][27][28][29]. In some cases, it has been demonstrated that the inhibitors act through direct binding to the b1 domain of NRP1.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that other ligands containing a C-terminal arginine will also bind in a similar fashion [15]. Although protein-protein interactions have been considered challenging targets in drug discovery [16], a number of small molecules and peptides have been identified as inhibitors of the VEGF-A 165 -NRP1 interaction [17][18][19][20][21][22][23][24][25][26][27][28][29]. In some cases, it has been demonstrated that the inhibitors act through direct binding to the b1 domain of NRP1.…”
Section: Introductionmentioning
confidence: 99%
“…These include small molecules [16,17,18,19,20,21], VEGF 165 derived peptides [22,23], or cyclic peptides [24,25,26]. Another set of the inhibitors proposed so far consists of the peptide A7R (ATWLPPR) [27] and derivatives inspired by this sequence [28,29,30]. A7R exhibits a relatively good inhibition in in vitro tests with an IC 50 of 5.86 μM [24].…”
Section: Introductionmentioning
confidence: 99%
“…Conformational latitude -inhibitory activity relationship of KPPR tetrapeptide analogues (KxxR) [5] Several analogues (KxxR) with various conformational latitudes have been synthesized and found as inhibitors of NRP-1. Detailed insight provided by molecular dynamics simulation allowed forming a clear relationship between "flexibility" of the -xx-part (positions 2 and 3) of the molecules and their inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%